Automation of NCEI NOAA Meteorological Data Decoding and its use for the Analysis of Temperature Extremes in the Czech Republic (2010-2023) - Rouckova, Lenka (International Conference on Military Technologies (Online), 2025)
This study focuses on the analysis of meteorological data from five meteorological stations in the Czech Republic for the period 2010-2023. The aim was to automate the decoding of the data and evaluate its suitability for the analysis of temperature extremes. The data were obtained from NOAA's NCEI and processed using Python scripts to ensure efficient decoding. The results show high time series completeness (greater than 98.5 %) and identify locations with the highest occurrence of temperature extremes in the initial analysis. Kuchařovice shows the highest occurrence of high temperatures, while Přibyslav has the most days with extremely low temperatures. Future research should expand the data to include more variables and finer temporal resolution to better understand extreme weather patterns.